1984
DOI: 10.1111/1523-1747.ep12259181
|View full text |Cite
|
Sign up to set email alerts
|

Direct Effects of Minoxidil on Epidermal Cells in Culture

Abstract: Minoxidil, a potent antihypertensive agent, induces generalized hypertrichosis when administered systemically, or localized hair regrowth when applied topically to sites of severe alopecia areata. The pharmacologic mechanisms by which minoxidil stimulates hair growth are unknown. This study was designed to examine whether minoxidil has direct effects on neonatal murine epidermal cells in culture. In the presence of minoxidil, cultures showed a marked dose-dependent second peak of DNA synthesis 8-10 days after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
12
0
2

Year Published

1984
1984
2000
2000

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(20 citation statements)
references
References 11 publications
6
12
0
2
Order By: Relevance
“…We also found that high doses of Mi noxidil (1 mM ) has pro-differentiative prop erties, and similar results were described by Bernd et al [ 18] on HaCat keratinocytes with 1.2 mM Minoxidil. No effects on NHK differ entiation were observed with lower doses of Minoxidil, either by us or by others [14,17,18]. However, we showed that millimolar concentrations of Minoxidil are partially cy totoxic, in agreement with other reports [13][14][15]17], rendering this pro-differentiative ef fect difficult to interpret.…”
Section: Minoxidil On Nhk Prolifcration/differentiationsupporting
confidence: 89%
See 4 more Smart Citations
“…We also found that high doses of Mi noxidil (1 mM ) has pro-differentiative prop erties, and similar results were described by Bernd et al [ 18] on HaCat keratinocytes with 1.2 mM Minoxidil. No effects on NHK differ entiation were observed with lower doses of Minoxidil, either by us or by others [14,17,18]. However, we showed that millimolar concentrations of Minoxidil are partially cy totoxic, in agreement with other reports [13][14][15]17], rendering this pro-differentiative ef fect difficult to interpret.…”
Section: Minoxidil On Nhk Prolifcration/differentiationsupporting
confidence: 89%
“…No effects on NHK differ entiation were observed with lower doses of Minoxidil, either by us or by others [14,17,18]. However, we showed that millimolar concentrations of Minoxidil are partially cy totoxic, in agreement with other reports [13][14][15]17], rendering this pro-differentiative ef fect difficult to interpret. On an other hand, such high concentrations are poorly relevant to in vivo data (maximal plasmatic levels of Minoxidil after systemic administration of hair growth-promoting doses: 0.775 \iM), but we cannot exclude an accumulation of drug in some compartments of the follicle, especially the hair shaft rich in keratins and melanin [42].…”
Section: Minoxidil On Nhk Prolifcration/differentiationsupporting
confidence: 89%
See 3 more Smart Citations